The Effect of Adding Probiotics Lactobacillus acidophilus, Lactobacillus plantarum and Lactococcus lactis on The Quantity and Quality of Layer Eggs Isa Brown - Chozin, Aminullah Alhady; Yunita, Maya Nurwartanti; Dhamayanti, Yeni; Kuncorojakti, Suryo; Prastiya, Ragil Angga; Wibawati, Prima Ayu (Universitas Airlangga, 2022)
Laying breeds of chickens or commonly called layers are a breed of chicken that has potential value as an egg producer. The length of the layer production period is 80 – 90 weeks. During layer production, layers require high energy to produce, while the level of energy in the ration determines layer consumption. Various efforts have been made to increase the efficiency of using chicken feed in tropical areas, one of which is the use of additional feed additives. Feed additives that can be used are probiotics which come from microorganisms such as Lactobacillus acidophilus, Lactobacillus plantarum and Lactococcus lactis. This research aims to determine the effect and potential of adding a combination of probiotics Lactobacillus acidophilus, Lactobacillus plantarum, and Lactococcus lactis in increasing the quantity and quality of layer eggs during the production period. This research is experimental using a Completely Randomized Design (CRD). This study used a layer population of 20 individuals from the Isa Brown strain aged 40 weeks which were divided into four groups consisting of P1, P2, P3 and P4 with each group consisting of 5 individuals. The data that was collected was analyzed using Analysis of Variance (ANOVA) using SPSS version 24.0 software, then continued with the Duncan test on the data which showed significant differences (P<0.05). Based on the results of the study, the addition of the probiotics Lactobacillus acidophillus, Lactobacillus plantarum, and Lactococcus lactis in drinking water at doses of 2 mL/L, 4 mL/L, and 6 mL/L cannot increase the quantity of layer eggs, but can improve the external quality of layer eggs (egg weight, egg length, egg diameter, shell weight, shell thickness), and can improve the internal quality of layer eggs (yolk score, egg yolk index, egg white index, and haugh unit).